Pengembangan Media Pembelajaran Puzzle Untuk Meningkatkan Keterampilan Menulis pada Pembelajaran Bahasa Indonesia Materi Teks Deskriptif di Sekolah Dasar - Indriani, Novi; Yanti, Prima Gusti (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
This research aims to develop learning media in the form of Puzzles to improve writing skills and find out the suitability of Puzzle media in class IV Indonesian language learning at Muhammmadiyah Cibinong Elementary School which is valid and practical for use in learning activities. The research method is R & D (Research and development), with the ADDIE development model used analysis, design, development, implementation and evaluation. Based on the results of research analysis obtained from material experts, they obtained a score of 88% in the "Very Decent" category and media experts obtained a score of 93% which met the "Very Good" criteria. Then the practical results of the small group of students with a score of 86.5% and the large group with a score of 87.5% with valid results. So it can be concluded that Puzzle media to improve writing skills in learning Indonesian descriptive text is suitable for use in classroom learning activities.